Evaluating Metabolic Profiling of Human Milk Using Biocrates MxP® QUANT 500 Assay - Daniela Hampel; Setareh Shahab-Ferdows; Gilberto Kac; Lindsay H. Allen (Metabolites)
Background/Objectives: Metabolic profiling of human milk (HM) is indispensable for elucidating mother-milk-infant relationships. Methods: We evaluated the Biocrates MxP® Quant 500 assay for HM-targeted metabolomics (106 small molecules, 524 lipids) and analyzed in a feasibility test HM from apparently healthy Brazilian mothers (A: 2–8, B: 28–50, C: 88–119 days postpartum, ntotal = 25). Results: Of the 630 possible signatures detectable with this assay, 506 were above the limits of detection in an HM-pool (10 µL) used for assay evaluation, 12 of them above the upper limit of quantitation. Analyzing five different HM-pool volumes (2–20 µL) revealed acceptable linearity for 458 metabolites. Intraday accuracy of 80–120% was attained by 469 metabolites after spiking and for 342 after a 1:2 dilution. Analyzing HM from Brazilian mothers revealed significantly lower concentrations in colostrum vs. mature milk for many flow-injection analyses (FIA) and only a few LC-MS metabolites, including triglycerides, sphingomyelins, and phosphatidylcholines. Higher concentrations at the later lactation stages were found predominantly for amino acids and related compounds. Conclusions: The MxP Quant® 500 assay is a useful tool for HM metabolic profiling, minimizing analytical bias between matrices, and enhancing our ability to study milk as a biological system.